Protestant Christian Cultural Initiatives in the Suiyuan Region - LIU Chunzi, (Journal of Research for Christianity in China (JRCC), 2025)
Broadly speaking, the introduction of Christianity to China unfolded in four distinct phases: Nestorianism during the Tang Dynasty, the Yelüke'wen faith under the Yuan Dynasty, Catholicism in the late Ming and early Qing periods, and Catholicism alongside Protestantism in the late Qing era. During the late Qing period, missionary activities of both Catholicism and Protestantism reached their zenith in China. Most studies on the history of Christianity's development have primarily focused on Catholicism. Therefore, this paper focuses on organizing and researching the development of Protestant Christianity and its various missionary endeavors. It aims to provide a comprehensive understanding of Protestant development while also deepening recognition of Christianity as a whole. The primary subject of this study is the work of foreign missionaries in the Suiyuan region. By examining Christianity's intrinsic development, it objectively reflects the growth of Christianity in Suiyuan and documents its contributions to the area.
Keywords: Protestant Christianity Methods of Missionary Work Missionary Endeavors